2021
DOI: 10.2147/cia.s282709
|View full text |Cite
|
Sign up to set email alerts
|

Friends from the Future: A Scoping Review of Research into Robots and Computer Agents to Combat Loneliness in Older People

Abstract: Background and Aim: Loneliness is a common problem in older adults and contributes to poor health. This scoping review aimed to synthesize and report evidence on the effectiveness of interventions using social robots or computer agents to reduce loneliness in older adults and to explore intervention strategies. Methods: The review adhered to the Arksey and O'Malley process for conducting scoping reviews. The SCOPUS, PUBMED, Web of Science, EMBASE, CINAHL, PsycINFO, ACM Digital Library and IEEE Xplore databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 93 publications
(553 reference statements)
2
58
0
1
Order By: Relevance
“…Healthcare professionals have been working on different approaches to understand and detect loneliness amongst older adults [30,33,35,41]. In addition, evidence shows that healthcare professionals have implemented different interventions with positive effects on the prevention and management of loneliness amongst older adults [36,[78][79][80][81]. Despite this, loneliness is becoming an ever more complex public health problem, and it is necessary to tackle it urgently in a way that involves the whole of society [9,82].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals have been working on different approaches to understand and detect loneliness amongst older adults [30,33,35,41]. In addition, evidence shows that healthcare professionals have implemented different interventions with positive effects on the prevention and management of loneliness amongst older adults [36,[78][79][80][81]. Despite this, loneliness is becoming an ever more complex public health problem, and it is necessary to tackle it urgently in a way that involves the whole of society [9,82].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have also generally reflected the effectiveness of social robots in elderly care, including studies that address loneliness or social isolation [52,53], and the influence of smart houses on older adults' quality of life, including their effect on social isolation [54]. Recently, in the face of the COVID-19 pandemic, there has also been a stream of studies from different fields reviewing and considering the importance and possibilities of robots and computer agents in alleviating loneliness [55][56][57][58]. To the best of our knowledge, no prior studies have focused on role of physical ICT solutions in assessing and combating loneliness and social isolation among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review on robot-facilitated loneliness interventions found evidence supporting their use with older adults [ 30 ]. For example, Paro, a companion robot in the form of a fluffy baby harp seal, alleviated feelings of loneliness in older adults in nursing homes by providing direct companionship in a manner akin to a pet [ 31 ].…”
Section: Introductionmentioning
confidence: 99%